The Effect of Risk Management, Firm Age, and Firm Size on the Performance of Banking Companies Registered in Indonesia Stock Exchange Moderated By Corporate Governance and Budget as Control Variable - Mochamad Muslih; Serina Oktavia Marbun (International Journal of Science and Society, 2020)
The purpose of this study was to study the effect of risk management, company age, and company size on the performance of banking companies listed on the Indonesia Stock Exchange with governance as moderating and budget as control variables. This study uses quantitative methods with multiple regression analysis methods. The population of this study is banking companies listed on the Indonesia Stock Exchange for the period 2013 - 2018. The sample size is 28 (twenty eight) banking companies listed on the Indonesian Effek Exchange for the observation period of 6 (six) years. The data source is secondary data in the form of annual reports of banking companies listed on the Indonesia Effek Exchange. The results showed that risk management with a prob of 0.0003 (<0.05) and company size with a prob of 0.0002 (<0.05) had a significant positive effect on company performance. While the age of the company with a probability of 0.4967 (> 0.05) has no significant effect on company performance. Governance does not moderate the effect of risk management on company performance with a probability of 0.8623 (> 0.05), does not moderate the influence of company age on company performance with a probability of 0.3949 (> 0.05), and does not moderate the effect of firm size on company performance with probability of 0.0668 (> 0.05).